Helicoverpa armigera: An emerging pest of menthol mint in India - Kedar, Santosh C.; Navik, Omprakash; Navik, Omprakash; Kumaranag, K. M.; Suroshe, Sachin (Indian Horticulture, 2024)
Menthol mint (Mentha arvensis L.), an important medicinal and aromatic crop extensively cultivated across various states in India, holds substantial economic importance, particularly for smallholder farmers due to its profitability and high demand for essential oil in industries such as pharmaceuticals, cosmetics, and flavours. The cultivation of menthol mint in India faces a significant threat fromHelicoverpa armigera (Lepidoptera: Noctuidae), commonly known as the American bollworm, which inflicts severe damage during the early to mid-vegetative growth stages. This nocturnal pest defoliates the crop, impacting yields and profitability. Implementing integrated pest management strategies, including cultural, mechanical, biological, and chemical controls, is crucial to mitigate its impact and ensure sustainable menthol mint production.